The Impact of COVID-19 on Mental Healthcare Utilization in Switzerland Was Strongest Among Young Females-Retrospective Study in 2018-2020 - Yael Rachamin; Yael Rachamin; Levy Jäger; Reka Schweighoffer; Andri Signorell; Caroline Bähler; Carola A. Huber; Carola A. Huber; Eva Blozik; Eva Blozik; Erich Seifritz; Thomas Grischott; et al. (Frontiers Media S.A., 2023)
Objectives: To provide a thorough assessment of the impact of the COVID-19 pandemic on the utilization of inpatient and outpatient mental healthcare in Switzerland.Methods: Retrospective cohort study using nationwide hospital data (n > 8 million) and claims data from a large Swiss health insurer (n > 1 million) in 2018-2020. Incidence proportions of different types of psychiatric inpatient admissions, psychiatric consultations, and psychotropic medication claims were analyzed using interrupted time series models for the general population and for the vulnerable subgroup of young people.Results: Inpatient psychiatric admissions in the general population decreased by 16.2% (95% confidence interval: −19.2% to −13.2%) during the first and by 3.9% (−6.7% to −0.2%) during the second pandemic shutdown, whereas outpatient mental healthcare utilization was not substantially affected. We observed distinct patterns for young people, most strikingly, an increase in mental healthcare utilization among females aged <20 years.Conclusion: Mental healthcare provision for the majority of the population was largely maintained, but special attention should be paid to young people. Our findings highlight the importance of monitoring mental healthcare utilization among different populations.